MEMÓRIA SOCIAL E CIDADE CONTEMPORÂNEA: O VELHO CENTRO FERROVIÁRIO DE PONTA GROSSA – PR - Madalozzo, Nisiane (2015)
Ponta Grossa is a Brazilian city that has historically had its development related to privileged geographic location. The railroad has been one of the historical events which contributed significantly for its urbanization. The railroad patio, unveiled in the transition from ninth to twentieth century, has defined the pattern of urban development, being influential to the perception of the local community as well, especially related to the cosmopolite idea of progress the city has been subjected to since then. However, with the further creation of a second railroad patio out of the central area and subsequent removal of rails, the old „railroad center‟ has lost its characteristics, with new built equipment and consequent different significations related. The main goal of this research is analyzing the current composition of the area first known as Ponta Grossa railroad center, from the signification of its built elements for the native society. The hypothesis put is that not all members of the community that live in the city are able to recognize and attribute importance to the railroad heritage of Ponta Grossa by experiencing the former patio. The document is divided in four chapters. In the first one, theoretical consideration is exposed. Especially the concepts of local and topofilia are studied, for being appropriate to the object studied. Then, both spatial and historical contextualizing are offered. Methodologically, there has been fragmentation of the studied object into ten different built elements, which are presented on the third chapter. Such decision has been important as to make data treatment viable, it being realized threw surveys and interviews with open answers. Representatives of different social groups have been included. In the forth chapter, the interviewing methods are presented, as are the results. As a conclusion, the methodology applied has proven adequate, allowing to comprehend the thoughts of people with different social profiles about the former railroad patio. The valuating of railroad historic elements has shown relative to specific social profiles, as expected; there has been, however, more recognizing of the importance of historical heritage than previously expected. It was also possible to identify that, through massive participation of the community on open-answer types of survey, a substantial array of conclusions is possible – that being thus considered as methodological contribution for the academy.